Sodium Hydride Induced N-Arylation of Diisopropyl Azodicarboxylate by Aryl Trifluoromethanesulfonates - Yavari, Issa; Ghazanfarpour-Darjani, Majid; Bayat, Mohammad J.; Malekafzali, Alaleh (Synlett, 2015)
A method for intermolecular N-arylation of the anionic species derived from diisopropyl azodicarboxylate and sodium hydride by aryl trifluoromethanesulfonates, in the presence of a ligand-free copper(I) oxide catalyst at 80 °C in N,N-dimethylformamide, is reported. A variety of functionalized aryl triflouromethanesulfonates were efficiently coupled by this method.
Keywords: C–N cross-coupling; aryl trifluoromethanesulfonates; diisopropyl azodicarboxylate; copper(I) oxide